PEMANFAATAN LAHAN PEKARANGAN MELALUI KONSEP RUMAH PANGAN LESTARI UNTUK BUDIDAYA TANAMAN SAYUR DI POSYANDU DUA DARA, DESA AIK DEWA - Ramadhan, Sahru; Wirayuda, Lalu Ahmad; Zulbiantoni, Danil; Meizora, Berlian Caterine; Budiyanti, Ameliya Eka; Septianingsih, Inda; Putri, Vira Alfiana; Melani, Ria; Qibtia, Hesti Nurul; Sani, Usman; Nurmayanti, Siti (Universitas Mataram, 2024)
Aik Dewa Village, as a part of Pringgasela, East Lombok Regency, West Nusa Tenggara, is a village that attracted attention to improve the community welfare, especially in fulfilling nutrition. This article describes the uniqueness and challenges that exist in this village, including the obstacles faced by the local community in accessing the quality of vegetables. Most of the yard land in the village has not been optimized, and it causes a lack of public awareness of its potential. The effort to optimize their yard land for horticultural farming is a solution to this problem by educating and motivating the community through the concept of Rumah Pangan Lestari (RPL). This Rumah Pangan Lestari activity was carried out by KKN students from University of Mataram and involved the participation from the locals and PKK community. The focus of this activity was cultivate the vegetable plants in the grounds of Posyandu Dua Dara, South Aik Dewa, using discussion and demonstration activities method. The results of this activity included making a planting medium that involves soil fermentation, making the greenhouse that is good for the environment, and planting the vegetable seeds in the area. It is expected that this activity can increase the public awareness of the importance of sustainable agriculture so they can contribute to the local food security. Keywords: Aik Dewa village, Rumah pangan lestari, Yard land